Latest Advances in High Brightness Disk Lasers. Issue 2 (April 2014) - Schad, Sven‐Silvius; Stolzenburg, Christian; Michel, Knut; Sutter, Dirk
Abstract For years disk lasers have been an ideal choice for the vast majority of high power material processing applications in the CW as well as short and ultra short pulse regime since they combine high output power with high beam quality at low investment and running cost. Ease of operation combined with highest efficiency, precision and robustness have established the disk laser as a standard tool throughout industrial applications. Tailoring laser based manufacturing chains has opened up a manifold of different areas such as high speed cutting, remote welding, brazing, cladding and hybrid welding.